Numerical evaluation of the duodenal mucosal resurfacing technique for the treatment of Type 2 diabetes. (November 2021) - Loiola, Bruna R.; Scofano Neto, Francesco; Guedes, Rodrigo O.C.
Highlights: Bioheat transfer equation is employed as a thermal model of the DMR treatment. Assessment of tissue thermal damage induced by the ablation process. DMR procedure is capable of thermally affecting the mucosal layer of the duodenum. Thermal damage is restricted to the submucosal layer in the lifting procedure. Muscularis propria region may be thermally affected without lifting stage Abstract: Backgrounds and objectives: This work presents a numerical analysis of the Duodenal Mucosal Resurfacing (DMR) technique, which is a relatively new treatment for Type 2 diabetes that has been already tested in human beings. In this innovative strategy, an endoscopic catheter is placed inside the duodenum thus serving as a guide to an ablation device. A circumferential ablation is then performed by using a balloon filled with a hot fluid with pre- and post-cooling stages that allows for a controlled thermal procedure. Clinical outcomes indicate that the damaged duodenal lining induces a better control of glycemic levels. Therefore, a numerical evaluation of the efficiency of this treatment is carried out by utilizing the bioheat transfer equation in the transient form. Methods: The finite volume method is used in the discretization of the energy equation and the results are verified by exploring the same mathematical model in a commercial finite-element package. The Arrhenius criterion for the evaluation of the thermally affected tissue is employed in this study. Results: A systematic analysis of the simulations is performed by investigating two scenarios: one in which the lifting of the mucosal duodenum layer is achieved and another one where the lifting strategy is not implemented. The role of the magnitude of the blood perfusion coefficient, tissue thermal conductivity, peak, pre- and post-cooling temperatures is thoroughly explored, especially in connection with the evaluation of the extent of the thermally affected region. Conclusions: According to the simulations discussed in the present contribution, this treatment is capable of accurately targeting the cells in the mucosal layer without significantly affecting the outermost stratum of the organ if the lifting process is applied. However, for the case without lifting, the muscularis propria layer may reach temperatures above 42 °C during a short time interval and thus the treatment should be considered with caution by the physician.